Social Dynamics Covid-19 and Student Perceptions in Papua - Sawir, Muhammad; Qomarrullah, Rif'iy; Pakasi, Usman; S, Lestari Wulandari (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The social dynamics faced by the people of Jayapura City related to the Covid-19 outbreak, namely increasing anxiety and even fear of the sound of ambulance sirens carrying patients so that a negative stigma appears on residents exposed to the virus. The purpose of the research carried out is to describe and analyze student perceptions as part of the community regarding the knowledge, handling, and sound of the Covid-19 ambulance siren especially in Jayapura City, in July 2021. This research is a quantitative study using a cross-sectional design, a sample totaling 63 Cenderawasih University students obtained from direct interviews as well as filling out questionnaires and google forms online. Data analysis used Chi-Square, univariate, bivariate, and multivariate with multiple logistic regression statistics. The univariate, bivariate, and multivariate values: (1) P=0.099, P=0.32, P=0.486, P=0.242, P=0.996, P=0.066, means that there is no relationship between age and gender with student perceptions of Covid-19; (2) P=0.000, P=0.005, there is a relationship between knowledge about Covid-19 and students’ perceptions of vaccines; (3) P=0.411, P=0.715, there is no relationship between gender and age with students’ perceptions of handling Covid-19; (4) P=0.593, P=0.000, there is no relationship between students’ perceptions of the ambulance siren sound. Based on the results of the discussion in this study, namely: (1) Respondents have good knowledge or understanding of the endemic Covid-19 virus; (2) Most of the respondents saw the handling of Covid-19 in the fairly good range of categories; and (3) Respondents generally have a bad perception of the sound of ambulance sirens passing by carrying Covid-19 patients. Knowledge of influencing student perceptions is needed to provide comprehensive and equitable information to all communities about handling, prevention, and all information regarding joint efforts in overcoming COVID-19 in Papua.